Pengembangan Strategi dan Metode Pembelajaran Pendidikan Agama Islam - ., Jeprianto; ., Herwani (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2021)
Strategy is a very influential component in the world of education, one of which is in the learning process of islamic religious education. This islamic religious education learning strategy is one of the efforts to apply how the values of islamic teachings that axist in eact material can be learned, understood and can be practiced by students in veryday life. In this case strategies and methods in learning are needed by an aducator because strategies and methods are tools or ways to make it easier for an educator to convey learning material so that the results obtained re in accordance with what the educator wants to expect. Therefore strategies and methods must go hand in hand in the teaching process.